Determinan Kejadian Preeklampsia Berat pada Ibu Hamil di Rumah Sakit Ibu Anak Anugrah Kubu Raya Kalimantan Barat - Puji Rahayu Lestari; Fatya Nurul Hanifah; Selasih Putri (Jurnal Ventilator, 2024)
Background: The highest cause of maternal death is hypertension in pregnancy which includes severe preeclampsia or what we know as PEB. Preeclampsia itself is a pregnancy condition that has problems characterized by hypertension, protein in the urine, and edema that occurs in pregnant women at 20 weeks. If the preeclampsia condition worsens and does not receive proper treatment, pregnant women can experience eclampsia with additional symptoms of seizures. Research Objective: To determine the most influential determinants of the incidence of severe preeclampsia in pregnant women at RSIA Anugrah Kubu Raya. Method: This study used a case-control study design with a retrospective approach. The study sample consisted of 76 respondents (38 controls and 38 cases). Data analysis used logistic regression tests. The study was conducted at RSIA Anugrah Kubu Raya. Results: The most influential determinants were a history of hypertension and a history of preeclampsia. Conclusion: The most influential variable in the incidence of preeclampsia was a history of preeclampsia.